Effect of phenytoin and age on gingival fibroblast enzymes. - Surena Vahabi; Bahareh Nazemisalman; Mojtaba Vahid Golpaigani; Anahid Ahmadi (Tehran University of Medical Sciences, 2014)
The alteration of cytokine balance is stated to exert greater influence on gingival overgrowth compared to the direct effect of the drug on the regulation of extracellular matrix metabolism. The current study evaluated the effect of phenytoin on the regulation of collagen, lysyl oxidase and elastin in gingival fibroblasts.Normal human gingival fibroblasts (HGFs) were obtained from 4 healthy children and 4 adults. Samples were cultured with phenytoin. MTT test was used to evaluate the proliferation and ELISA was performed to determine the level of IL1β and PGE2 production by HGFs. Total RNA of gingival fibroblasts was extracted and RT-PCR was performed on samples. Mann-Whitney U test was used to analyze the data with an alpha error level less than 0.05.There was a significant difference in the expression of elastin between the controls and treated samples in both adult and pediatric groups and also in the lysyl oxidase expression of adult controls and treated adults. No significant difference was found between collagen expression in adults.The significant difference in elastin and lysyl oxidase expression between adult and pediatric samples indicates the significant effect of age on their production.